Dietary intake of Rubrivivax gelatinosus biomass enhances phagocytic cells in tropical fish Piaractus mesopotamicus infected with Aeromonas hydrophila - Gallani, S. U. [UNESP]; Valladão, G. M.R. [UNESP]; Kotzent, S. [UNESP]; Santo, E. F.E.; Ponsano, E. H.G. [UNESP]; Pilarski, F. [UNESP] (Springer Nature, 2019)
This study investigated the effects of prolonged administration of immunostimulant biomass produced by the bacteria Rubrivivax gelatinosus on the innate immune system of pacu Piaractus mesopotamicus infected with Aeromonas hydrophila. Fish were supplemented for 2 months with diets containing 0 g kg −1 biomass (TR1), 0.5 g kg −1 biomass (TR2) and 1.5 g kg −1 biomass (TR3). Haematological, biochemical and immunological analyses were carried out before biomass supplementation and 24 h after the triggering of its immune system with sub-lethal doses of A. hydrophila. As planned, no mortality was recorded in any group. After the bacterial challenge, fish from all groups showed a decrease (p < 0.05) in thrombocytes and lymphocytes and increase (p < 0.05) in monocytes, neutrophils and positive granular leucocyte (PAS-GL). Also, infected fish showed a decrease (p < 0.05) in glucose, protein, albumin and globulin and an increase (p < 0.05) in ALT and AST levels. Burst was higher (p < 0.05) after infection. The most relevant results were the increase (p < 0.05) of about 100% in monocytes and 50% in neutrophils in the group with the highest biomass supplementation compared with the control. These results suggest that incorporation of R. gelatinosus biomass into the diet for 60 days before exposure to a stress factor increases important cells involved in defence in the innate immune system.
Keywords: Aquaculture; Biotechnology; Carotenoid; Dietary supplementation; Effluent treatment, Immunology